2022
DOI: 10.1002/advs.202105811
|View full text |Cite
|
Sign up to set email alerts
|

Acute Myeloid Leukemia Cells Educate Mesenchymal Stromal Cells toward an Adipogenic Differentiation Propensity with Leukemia Promotion Capabilities

Abstract: Mesenchymal stromal cells (MSCs) are essential elements of the bone marrow (BM) microenvironment, which have been widely implicated in pathways that contribute to leukemia growth and resistance. Recent reports showed genotypic and phenotypic alterations in leukemia patient-derived MSCs, indicating that MSCs might be educated/reprogrammed. However, the results have been inconclusive, possibly due to the heterogeneity of leukemia. Here, the authors report that acute myeloid leukemia (AML) induces MSCs towards an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 69 publications
0
23
0
2
Order By: Relevance
“…The progression of leukemia is guaranteed by the exosomes produced by the AML cells that facilitate the engraftment of AML and allow the communication of leukemia cells with their microenvironment, as well as inducing oncogenic factors such as c-Myc. [25,28]. Furthermore, the release of exosomes leads to the production of immune-inhibiting cytokines, thus ensuring the growth and survival of cancer cells.…”
Section: Acute Myeloid Leukemiamentioning
confidence: 99%
“…The progression of leukemia is guaranteed by the exosomes produced by the AML cells that facilitate the engraftment of AML and allow the communication of leukemia cells with their microenvironment, as well as inducing oncogenic factors such as c-Myc. [25,28]. Furthermore, the release of exosomes leads to the production of immune-inhibiting cytokines, thus ensuring the growth and survival of cancer cells.…”
Section: Acute Myeloid Leukemiamentioning
confidence: 99%
“…Leukemic cells and leukemic stem cells reside in the bone marrow and lymphatic niches that resemble a glucose-deprived and hypoxic TME, which is comparable to the conditions seen in solid tumors. Two recent studies demonstrated that acute myeloid leukemia (AML) cells remodel their direct environment by secretion of exosomes that, in turn, promote MSC differentiation towards adipocytes and lipolysis in already differentiated adipocytes [ 56 , 57 ]. Moreover, adipose tissue is beneficial for AML blasts and leukemic stem cells (LSCs) by increasing FAO and CD36/FABP4 expression, resulting in the prevention of serum starvation-induced apoptosis and protection from chemotherapy [ 58 , 59 ].…”
Section: Sources Of Lipids Within the Tumor Microenvironmentmentioning
confidence: 99%
“…It was reported that the bone marrow (BM) microenvironment could be remodelled into a hospitable niche supporting leukaemogenesis and impeding normal haematopoiesis in leukaemias 2,3 . BM mesenchymal stromal cells (BM‐MSCs), a heterogeneous, essential population of the BM niche, are reported to play different roles in the AML BM niche 4–6 . Zhang et al 4 reported that AML induced MSCs towards an adipogenic differentiation propensity, leading to greatly enhance leukaemia engraftment, which represented an opportunity for novel therapeutic strategies based on targeting AML cells–MSCs communication.…”
Section: Introductionmentioning
confidence: 99%
“…BM mesenchymal stromal cells (BM‐MSCs), a heterogeneous, essential population of the BM niche, are reported to play different roles in the AML BM niche 4–6 . Zhang et al 4 reported that AML induced MSCs towards an adipogenic differentiation propensity, leading to greatly enhance leukaemia engraftment, which represented an opportunity for novel therapeutic strategies based on targeting AML cells–MSCs communication. Another two studies also found that AML cells establish physical connections with MSCs facilitating leukaemia progression 5,6 .…”
Section: Introductionmentioning
confidence: 99%